Empowering Healthcare Agility: A Strategic Framework for Pandemic-Responsive Operational Planning - Alrabghi A; Tameem A (Journal of Multidisciplinary Healthcare, 2025)
Abdullah Alrabghi,1 Abdullah Tameem2 1Department of Industrial and Systems Engineering, University of Jeddah, Jeddah, Saudi Arabia; 2Department of Industrial Engineering, Jeddah International College, Jeddah, Saudi ArabiaCorrespondence: Abdullah Alrabghi, Department of Industrial and Systems Engineering, College of Engineering, University of Jeddah, 6420 University of Jeddah Road, P.O. BOX 13151, Jeddah, 21493, Saudi Arabia, Tel +966 1 2233 4444, Email aalrabghi@uj.edu.saIntroduction: The COVID-19 pandemic has challenged healthcare systems globally, testing their resilience due to sudden fluctuations in confirmed cases, intensive care unit utilization, and medical team availability. These dynamics forced healthcare facilities to continuously adapt their operational plans.Methods: This research conducts a comprehensive review of published changes implemented by various healthcare facilities in response to the pandemic.Results: The study provides new insights into enabling healthcare agility during pandemics such as COVID-19. A decision-making framework is proposed to assist hospital management in exploring and selecting appropriate alternatives, allowing faster adaptation in dynamic environments.Discussion: The framework can be tailored to each hospital’s unique characteristics and the prevailing epidemiological situation. Future research could explore the use of simulation to automate the development of dynamic operational plans based on pre-selected criteria, further enhancing healthcare responsiveness. Keywords: healthcare, dynamic, planning, COVID-19, pandemic